Influence of histochemical stains on DNA obtained from FFPE samples - Boghenco, O. (2018)
Introduction: Formalin-fixed, paraffin embedded (FFPE) samples are used for diagnostic and prognostic purposes. Histopathological analysis frequently includes not only histomorphological evaluation but also histochemical and molecular studies. In some cases FFPE samples are scarce and it is necessary to use the same histological section for histochemical analysis and DNA extraction. In molecular pathology labs this is a common practice, allowing the analysis of DNA specifically from altered cells. However, histochemical techniques use reagents that may induce chemical modifications on DNA. To perform a literature review about the influence of histochemical stains on DNA integrity. Materials and methods: PubMed and Research Gate were used to survey original articles published until December 2017. Results: For this review articles about the analysis of DNA extracted from stained FFPE sections were considered. The studies demonstrated that: DNA extracted from sections stained with Azure B, toluidine blue and methyl green (MG) was successfully amplified by Polymerase Chain Reaction (PCR) whereas Mayer’s hematoxylin stain inhibits the reaction. Another study demonstrated that DNA amplification by PCR had better results with eosin Y and MG stains comparatively to Mayer’s hematoxylin and May-Grunwald. Banaschak et al. showed that DNA analysis by PCR and capillary electrophoresis was successful with Hematoxylin-Eosin (HE), Periodic Acid Schiff (PAS), Azan and Perl's stains. Phosphotungstic acid hematoxylin (PTHA) and Gomori stains had negative results. Two different studies concluded that DNA is refractory to HE stain as capillary electrophoresis demonstrated similar degradation to that of unstained samples and it was successfully amplified by PCR. Conclusions: Histochemical analysis allows demonstration of cellular components whose alterations are typical from pathological conditions. These techniques encompass reagents that may alter biomolecules. Nevertheless, from the analyzed studies it is possible to conclude that DNA integrity is maintained in techniques such as Azure B, toluidine B, MG, eosin Y, HE, PAS, Azan and Perls. On the other hand, Mayer’s hematoxylin, May-Grunwald, PTHA and Gomori resulted in inhibition of DNA amplification. Since this analysis was not performed in common routine techniques such as Masson’s Trichrome and PAS-Alcian Blue, it is important to deepen the knowledge, performing new studies for future appliance.